Fluid responsiveness in pediatrics: an unsolved challenge - Escribá Alepuz, F.; Díaz Ruz, A.; Jiménez Santana, J. D.; García Cebrián, C.; Encarnación, J.; Hervías Sanz, M.; Argente Navarro, P. (Frontiers in Anesthesiology, 2024)
Predicting fluid responsiveness is a major challenge in the pediatric population as vascular and pulmonary compliance differ from the adults. However it is a crucial thing to avoid the harmful fluid overload. We count on different variables to identify responders being the dynamic parameters the ones with more evidence, specially the Respiratory Variation In Aortic Blood Flow Velocity based on echocardiography. Other variables rely on the arterial waveform, like Pulse Pressure Variation or Stroke Volume Variation seem to have limitations but new tests like VTC are arriving to overcome their drawbacks. We review the actual evidence regarding fluid responsiveness prediction in children and the anatomic and physiologic peculiarities of children that explain why they do not respond like adults and why we should study them in particular.